1992
DOI: 10.1159/000463416
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to Laboratory Animals and Small-Airway Hyperreactivity

Abstract: Fifty-six laboratory-animal workers were investigated regarding allergy and lung function. Thirty percent had at least one positive skin prick test against laboratory animals. RAST® test was positive in 25%. Thirty-two percent had laboratory-animal allergy (LAA; rhinoconjunctivitis and/or asthma). Association with an increased risk for LAA was found for atopy, as indicated by a family history of allergy, positive skin prick test against nonlaboratory environmental allergens, positive Phadiatop®, and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1993
1993
1995
1995

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…We have also found that sensitisation to animals is associated with small airway hyperreactivity [28], In another follow-up study of 38 workers, the animal-sensitised subjects showed significantly increased airway reactivity com pared to non-sensitised subjects [34].…”
Section: Clinical Picture and Allergy Work-upmentioning
confidence: 78%
See 4 more Smart Citations
“…We have also found that sensitisation to animals is associated with small airway hyperreactivity [28], In another follow-up study of 38 workers, the animal-sensitised subjects showed significantly increased airway reactivity com pared to non-sensitised subjects [34].…”
Section: Clinical Picture and Allergy Work-upmentioning
confidence: 78%
“…There ap pears to be an immunological difference between LAA analysis and the gene locus has been assigned to chromo some 1 lq [54]. We have found that atopy indicators such as parental and childhood allergy, raised total serum IgE level and positive skin prick tests against environmental allergens increase the risk of developing LAA [8,28,31], Through the use of these indicators of atopy, LAA asthma could be predicted with 50% sensitivity and 100% specificity in the last study. This was in contrast to LAA rhinitis where the indicators were unable to discriminate symptom cases from symptom-free subjects.…”
Section: Incidence Of Laamentioning
confidence: 82%
See 3 more Smart Citations